Draft Annual Plan 1994-95 Government of Gujarat - Planning Commission (Planning Commission, 1993)
Water resources available in the State for irrigation are relatively limited. Nearly two-third of the population in the State depends on agriculture which is essentially rainfed hardly 27 percent of the cultivable land has irrigation facilities. The total ultimate irrigation potential from surface as well as ground water is assessed at 64.88 lakh hectares By the end of March, 1993, irrigation potential of about 33.86 (approximately) lakh hectares has been created.
Government of Gujarat, General Administration Department Planning Division